Pendekatan Konstruktivisme dalam Al-Qur’an (Studi Pedagogis terhadap Kisah Nabi Ibrahim Mencari Tuhan) - Izzatur Rusuli; Zakiul Fuady Muhammad Daud; Supiah Supiah (Al-Ulum, 2022)
The story of the spiritual journey of the Prophet Ibrahim AS in seeking his Lord in the Qur’an contains the seeds of constructivism approach. This article aims to know how the concept of constructivism approaches, how the spiritual journey of Prophet Ibrahim AS in seeking his Lord and how the constructivism approach practiced by the Prophet Ibrahim AS in his journey. This research is a qualitative study with a literature review approach by using primary and secondary data sources and content analysis as a data analysis technique. The results of this research show that the concept of constructivism is a concept of a learning approach that emphasizes the active of learners to build their own knowledge and involve social interactions. Meanwhile, the spiritual journey of the Prophet Ibrahim AS in seeking his Lord was depicted in the surah al-An'am verse 76-79 in which the Prophet Ibrahim AS made the star, moon, sun as God. However, he got to the truth that the true God is the God who created it all. The application of the constructivism approach conducted by the Prophet Ibrahim AS appeared at the prophet Ibrahim's attempt to construct his own knowledge with various sources about the concept of deity that ultimately, he found the true truth.